\(a,x=0,25=\dfrac{1}{4}\Leftrightarrow\sqrt{x}=\dfrac{1}{2}\\ \Leftrightarrow A=\dfrac{2+\dfrac{1}{2}}{\dfrac{1}{2}}=\dfrac{3}{2}:\dfrac{1}{2}=3\\ b,B=\dfrac{x-1+2\sqrt{x}+1}{\sqrt{x}\left(\sqrt{x}+1\right)}\left(x>0\right)\\ B=\dfrac{\sqrt{x}\left(\sqrt{x}+2\right)}{\sqrt{x}\left(\sqrt{x}+1\right)}=\dfrac{\sqrt{x}+2}{\sqrt{x}+1}\\ c,\dfrac{A}{B}\ge\dfrac{3}{2}\Leftrightarrow\dfrac{\sqrt{x}+2}{\sqrt{x}}\cdot\dfrac{\sqrt{x}+1}{\sqrt{x}+2}-\dfrac{3}{2}\ge0\\ \Leftrightarrow\dfrac{\sqrt{x}+1}{\sqrt{x}}-\dfrac{3}{2}\ge0\Leftrightarrow\dfrac{2-\sqrt{x}}{2\sqrt{x}}\ge0\\ \Leftrightarrow2-\sqrt{x}\ge0\left(2\sqrt{x}>0\right)\\ \Leftrightarrow\sqrt{x}\le2\Leftrightarrow x< 4\\ \Leftrightarrow0< x< 4\left(kết.hợp.ĐKXĐ\right)\)